2011
DOI: 10.1673/031.011.0114
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Susceptibility of Human Myiasis Caused by the New World Screw-Worm,Cochliomyia hominivoraxin São Gonçalo, Rio de Janeiro, Brazil

Abstract: This study was carried out between July 2007 and June 2008 and reports on the occurrence of human myiasis caused by the New World screwworm, Cochliomyia hominivorax (Coquerel) (Diptera: Calliphoridae) in São Gonçalo in the state of Rio de Janeiro, Brazil. Liquid or solid vaseline was used to suffocate the larvae, which were then preserved in 70% ethanol and sent to the Instituto Oswaldo Cruz for identification. C. hominivorax were identified in all 22 cases of myiasis. There were 12 male and 10 female patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
1
26
0
7
Order By: Relevance
“…In this study, the infestations of the patients were all on lower limbs. These results agree with the previous studies showing that the lower limbs were affected more frequently as reported by Nascimento et al (2005), Marquez et al (2007), and Batista-da-Silva et al (2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the infestations of the patients were all on lower limbs. These results agree with the previous studies showing that the lower limbs were affected more frequently as reported by Nascimento et al (2005), Marquez et al (2007), and Batista-da-Silva et al (2011).…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Dokur et al (2015) reported two cases of myiasis in rural areas of southeast Turkey. Abundant household animals and unhealthy environment also participate in the emergence of new cases of myiasis (Batista-da-Silva et al 2011). Thus, it should be considered as Ban occupational disease^among farmer and shepherds.…”
Section: Discussionmentioning
confidence: 99%
“…Nosocomial infestations may also imply broader negligence on the part of the hospital authorities and possible failures in the sanitary and structural conditions of the hospital. is negligence could be grounds for legal action, involving significant losses for hospitals if it is sued for negligence [27,28]. In our case, this was the first case of nosocomial myiasis at a specialty hospital.…”
Section: Discussionmentioning
confidence: 89%
“…Larvae can be deposited in the eye causing painful ophthalmomyiasis resembling a foreign body in the eye sensation. Inflammatory reaction at the site if larviposition due to mast cell activation and IgE production may limit larval development [30]. Larvae accidentally ingested in mouth can be present in oral cavity in the damaged gums and teeth spaces.…”
Section: Clinical Featuresmentioning
confidence: 99%